Communicating health—Optimising young adults' engagement with health messages using social media: Study protocol. Issue 5 (15th July 2018) - Lombard, Catherine; Brennan, Linda; Reid, Michael; Klassen, Karen M.; Palermo, Claire; Walker, Troy; Lim, Megan S.C.; Dean, Moira; Mccaffrey, Tracy A.; Truby, Helen
Abstract : Background: Obesity is a global health problem. Understanding how to utilise social media (SM) as a platform for intervention and engagement with young adults (YAs) will help the practitioners to harness this media more effectively for obesity prevention. Aim: Communicating health (CH) aims to understand the use of SM by YAs, including Aboriginal YAs, and in doing so will improve the effectiveness of SM strategies to motivate, engage and retain YAs in interventions to reduce the risk of obesity, and identify and disseminate effective ways for health professionals to deliver obesity prevention interventions via SM. Methods: The present study describes the theoretical framework and methodologies for the CH study, which is organised into four interrelated phases, each building on the outcomes of preceding phases. Phase 1 is a mixed methods approach to understand how YAs use SM to navigate their health issues, including healthy eating. Phase 2 utilises co‐creation workshops where YAs and public health practitioners collaboratively generate healthy eating messages and communication strategies. Phase 3 evaluates these messages in a real‐world setting. Phase 4 is the translation phase where public health practitioners use outcomes from CH to inform future strategies and to develop tools for SM for use by stakeholders and the research community. Discussion: The outcomes will include a rich understanding of psychosocial drivers and behaviours associated with healthy eating and will provide insight into the use of SM to reach and influence the health and eating behaviours of YAs.